Influence of Even-Order Dispersion on Super-Sech Soliton Transmission Quality under Coherent Crosstalk - Panajotovic, Aleksandra; Milovic, Daniela; Biswas, Anjan; Zerrad, Essaid (Research Letters in Optics, 2008)
The transmission speed of optical network strongly depends on the impact of higher order dispersion. In presence of coherent crosstalk, which cannot be otherwise controlled by optical filtering, the impact of higher order dispersions becomes more pronounced. In this paper, the general expressions, that describe pulse deformation due to second- and fourth-order dispersions in a single-mode fiber, are given. The responses for such even-order dispersions, in presence of coherent crosstalk, are characterized by waveforms with long trailing edges. The transmission quality of optical pulses, due to both individual and combined influence of second- and fourth-order dispersions, is studied in this paper. Finally, the pulse shape and eye diagrams are obtained.